Primary Male Breast Cancer: Analysis of Eight Cases and Review of Literature - Ahmed, JU; Hussain, MM (Journal of Bangladesh College of Physicians and Surgeons, 2007)
This is a hospital based retrospective study with 8 cases of newly diagnosed primary male breast cancer. Among 413 cases of breast cancer of both male and females, treated between 1988 to 2002 at Chittagong, eight were males. The incidence is 1.94%. The mean age of diagnosis is 50.13 years, which is later than females. A breast mass was the earliest, most important symptom. The duration of symptoms before treatment ranged from few weeks to years. Male breast cancer is of the same common pathologic types as in females that is 75% patients had duct cell carcinoma. The rarity of the tumor hinders the study of its biological behavior and etiology, which in consequence, are still not well understood. As with the female breast cancer, surgical excision followed by adjuvant CT, RT, hormone therapy are the treatment modalities. (J Bangladesh Coll Phys Surg 2007; 25 : 18-22)